Compositional and Textural Variations in Hainite-(Y) and Batievaite-(Y), Two Rinkite-Group Minerals from the Sakharjok Massif, Keivy Alkaline Province, NW Russia - Ekaterina A. Selivanova; Lyudmila M. Lyalina; Yevgeny E. Savchenko (Minerals, 2018)
Compositional and textural variations in the rinkite group, seidozerite supergroup minerals, batievaite-(Y), hainite-(Y) and close to them titanosilicates from the Sakharjok massif were studied. Statistical analysis allowed for defining two major substitution schemes leading to batievaite-(Y) and cation-deficient titanosilicates forming: Ca2+ + Na+ + F− ↔ □ + Y3+ + (OH)− and Ca2+ + Na+ ↔ □ + REE3+. Batievaite-(Y) and other cation-deficient titanosilicates are the earlier minerals formed by solid state transformation of the primary full-cation phase. Hainite-(Y) is a later mineral. It forms rims around earlier titanosilicates, or, less often, separate crystals.